Femmes et héroïne : bilan des connaissances, limites et perspectives nouvelles - Frigon, Sylvie (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1989)
This article gives the results of the consultation of several bases of bibliographical data on Women and Heroin, using the Boolean type of research. Various subjects are discussed, the extent of its use, the characteristics and factors of involvement in drug dependency, treatment, Mother/children relationship, Aids and prostitution. In the light of this survey of the literature, it seemed necessary to question the actual pertinence of these studies. They pose a number of important problems. Our criticism of the quality of these studies are I) problems of method and sampling; 2) epistemological problems and 3) the “monodisciplinarity” of these studies. In these works, the norm or “normality” (of drug addiction) is proper to the male sex. Women are considered marginal to this norm. Other fundamental omissions are mentioned, especially the relativity of the norms, problems connected with the concepts and the terms used. With regard to these various criticisms, we propose two models of analysis. The first refers to the study of women heroin-users as a group rather than in regard to men. The second is to construct a more general plan of analysis ofmarginality, of deviance and the criminality of women using the theories of social reaction in criminology and of radical materialist feminism. These two models could be complementary.